2023
DOI: 10.1097/mco.0000000000000896
|View full text |Cite
|
Sign up to set email alerts
|

The role of omega-3 polyunsaturated fatty acids in the intensive care unit

Abstract: Purpose of reviewThis review provides an update on the actions of omega-3 polyunsaturated fatty acids (PUFAs) and presents the most recent findings from trials in patients in the intensive care unit (ICU) setting including relevant meta-analyses. Many specialized pro-resolving mediators (SPMs) are produced from bioactive omega-3 PUFAs and may explain many of the beneficial effects of omega-3 PUFAs, although other mechanisms of action of omega-3 PUFAs are being uncovered. Recent findingsSPMs resolve inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…Our previous study demonstrated that early EPA treatment after percutaneous coronary intervention reduces acute inflammatory responses in patients with acute myocardial infarction 28) . Furthermore, previous studies showed a possible beneficial effect of omega-3 PUFAs on acute respiratory distress syndrome and sepsis 38) . In critically ill patients with acute respiratory distress syndrome, omega-3 PUFAs in enteral immunomodulatory diets may be associated with an improvement in early oxygenation and length in stay of intensive care 39) .…”
Section: Discussionmentioning
confidence: 97%
“…Our previous study demonstrated that early EPA treatment after percutaneous coronary intervention reduces acute inflammatory responses in patients with acute myocardial infarction 28) . Furthermore, previous studies showed a possible beneficial effect of omega-3 PUFAs on acute respiratory distress syndrome and sepsis 38) . In critically ill patients with acute respiratory distress syndrome, omega-3 PUFAs in enteral immunomodulatory diets may be associated with an improvement in early oxygenation and length in stay of intensive care 39) .…”
Section: Discussionmentioning
confidence: 97%
“…Various studies have indicated their role in the treatment of coronary heart disease, COVID-19, and organ damage when taken through diets (Singer & Calder, 2023). Additionally, there is evidence suggesting that the consumption of these fatty acids can reduce the risk of cancer (Gheorghe et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, after 6 days of HTNV infection, the levels of PUFA and glycerophospholipids decreased, indicating a possible reduction in energy production associated with disease progression. Omega-3 PUFAs, such as DHA and eicosapentaenoic acid (EPA), are known to reduce inflammation by promoting the synthesis of antiinflammatory eicosanoids and SPMs, such as resolvins, maresins, and protectins [39,40]. Thus, mice with low levels of unsaturated fatty acids due to HTNV infection would be more prone to an exacerbated inflammatory response.…”
Section: Discussionmentioning
confidence: 99%